Reliability constrained multi-period generation expansion planning of electrical energy resources using MILP - Aghaei, Jamshid; Roosta, Alireza; Akbari, Mohammad Amin; Rabiee, Abdorreza; Gitizadeh, M. (International transactions on electrical energy systems, 2013)
SUMMARY The main goal of Generation Expansion Planning (GEP) is to minimize total costs associated with new power generating units’ installation subject to technical and economical constraints. This paper addresses the GEP with probabilistic reliability criteria. The Loss‐of‐Load Probability reliability index is explicitly augmented as a new constraint which takes into account the reserve requirements. The outage cost is represented by the Expected Energy Not Served index. Due to nonlinear nature of these reliability indices, the GEP optimization problem with reliability criteria is very complicated to solve. Accordingly, the focus of this work is to deal with the reliability constrained multi‐period GEP problem as a Mixed Integer Linear Programming (MILP). The results in the case study indicate the effect of reliability considerations on decision‐making process. The simulation results also show the superiority of the proposed MILP‐based method in comparison with the well‐known metaheuristic algorithms and Dynamic Programming approach in the viewpoints of the accuracy and computational speed. Copyright © 2012 John Wiley & Sons, Ltd.